Classifying Different Types of Music Performance Anxiety - Spahn, Claudia; Krampe, Franziska; Nusseck, Manfred (Frontiers in Psychology, 2021)
Music performance anxiety (MPA) is a commonly present topic among musicians. Most studies on MPA investigated effects of a more general occurrence of MPA on performances. Less is known about individual variations of MPA within a performance, more specifically at the times before, during and after the performance. This study used a questionnaire to investigate these performance times in order to find out if there occur different types in the variation of the perceived MPA across the performance. The study was performed with 532 musicians; 27% of them being professional orchestra musicians, 45% non-professional orchestra musicians and 28% non-professional choir singers. The musicians were asked to fill in the Performance-specific Questionnaire for Musicians immediately after a performance. The questionnaire contains three scales regarding symptoms of MPA, functional coping with MPA and performance-related self-efficacy. A cluster analysis was performed on the PQM scales to identify systematic variations. Findings indicate that there are three different types of MPA in the sample studied. Type 1 describes musicians who have few symptoms of MPA throughout the performance, show functional coping with MPA, and have a stable and well-developed self-efficacy. Type 2 describes musicians who begin their performance with rather high symptoms of MPA but can positively reduce these by the end of the performance and show high values in self-efficacy and in functional coping. Type 3 contains musicians who begin their performance with some symptoms of MPA, which increase to the end of the performance. The values of self-efficacy and functional coping in this type are rather low. Of the total sample, half of the musicians were assigned to Type 1 and approximately a quarter each to Type 2 (27%) and Type 3 (23%). In accordance with the literature, the results confirm the importance of self-efficacy and functional coping for a positive performance experience.